Human Rights and Equitable Development: "Ideals", Issues and Implications - Decker, Klaus (Washington, DC: World Bank, 2012)
This paper outlines areas of human rights law relevant to development and introduces perspectives on the nature of the relationship between the two fields. While it is clear that some progress has been made towards integrating human rights and development, it is clear that the two discourses remain distinct, and attempts to find commonalities and convergence between them face numerous issues in practice. A key question for both human rights advocates and development practitioners is how human rights standards can be maintained in the context of development practices.